1995
DOI: 10.1159/000288951
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Study of Psychosocial Factors in 40-Year-Old Women with Essential Hypertension

Abstract: Most studies on essential hypertension have been performed in men. The aim of the present study was to describe psychosocial characteristics of 40-year-old women with never-treated essential hypertension. Psychosocial factors like childhood traumas, economy and education were studied, and psychological assessments of irritability, hostility, ‘John Henryism’ and type A behavior pattern carried out. Hypertensive premenopausal women (n = 29) were compared with healthy, age-matched, normotensive women (n = 18). Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
1
8
0
3
Order By: Relevance
“…These behavioral dimensions may be modified by the degree of alexithymia traits [30]. Still, our results support three previous reports on an association between alexithymia and hypertension [16][17][18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These behavioral dimensions may be modified by the degree of alexithymia traits [30]. Still, our results support three previous reports on an association between alexithymia and hypertension [16][17][18].…”
Section: Discussionsupporting
confidence: 91%
“…[11]). In line with these results, alexithymia was found to be significantly elevated in samples of newly diagnosed yet untreated hypertensive men and women [16,17]. Todarello et al [18] found 55.3% of patients with hypertension (n=114) to be alexithymic compared with 16.3% of nonhypertensive controls (n=130).…”
Section: Introductionmentioning
confidence: 76%
“…Using education to index SEP, they found support for the hypothesis among men, but not women. The remaining two, non-U.S. studies produced either null findings or did not test John Henryism by SEP interactions (Nordby et al, 1995;van Loon et al, 2001). Interestingly, there are strong parallels between John Henry, the legendary and determined 19th century African American unskilled worker and the widely embraced concept, among Finns, of "Sisu," generally defined as a special inner strength and determination to persist and overcome adversity even in the face of considerable odds (Kolehmainen, 1957;Lucas and Buzzanell, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…In this final model, blue-collar workers and farmers still had more than a two-fold higher rate of AMI compared to white-collar workers. This is one of few studies (Duijkers et al, 1988;Nordby et al, 1995;Somova et al, 1995;van Loon et al, 2001) to test the John Henryism hypothesis in a non-U.S. population. The first non-U.S. based study, conducted by Duijkers et al in 1988, used data from a small community sample of 20e59 year old Dutch men and women (Duijkers et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Such gender differences are likely to be due to gender roles in different societies. Recently, Nordby et al [6]have found that Norwegian hypertensive and normotensive women differed with regard to psychosocial factors. Alexithymia and difficulties in coping with aggression were more prevalent among the hypertensives, and the authors make the point that the psychosocial correlates of hypertension were not the same as for men in most published studies.…”
Section: Introductionmentioning
confidence: 99%